Impact of contrast injection and stent-graft implantation on reproducibility of volume measurements in semiautomated segmentation of abdominal aortic aneurysm on computed tomography. - Morin-Roy, Florence; Kauffmann, Claude; Tang, An; Hadjadj, Sofiane; Thomas, Olivier; Piché, Nicolas; Elkouri, Stéphane; Yang, Dan Yang; Therasse, Eric; Soulez, Gilles; Therasse, Éric (European Radiology, 2014)
Purpose: To assess the impact of contrast injection and stent-graft implantation on feasibility, accuracy, and reproducibility of abdominal aortic aneurysm (AAA) volume and maximal diameter (D-max) measurements using segmentation software.Materials and Methods: CT images of 80 subjects presenting AAA were divided into four equal groups: with or without contrast enhancement, and with or without stent-graft implantation. Semiautomated software was used to segment the aortic wall, once by an expert and twice by three readers. Volume and D-max reproducibility was estimated by intraclass correlation coefficients (ICC), and accuracy was estimated between the expert and the readers by mean relative errors.Results: All segmentations were technically successful. The mean AAA volume was 167.0 ± 82.8 mL and the mean D-max 55.0 ± 10.6 mm. Inter- and intraobserver ICCs for volume and D-max measurements were greater than 0.99. Mean relative errors between readers varied between -1.8 ± 4.6 and 0.0 ± 3.6 mL. Mean relative errors in volume and D-max measurements between readers showed no significant difference between the four groups (P ≥ 0.2).Conclusion: The feasibility, accuracy, and reproducibility of AAA volume and D-max measurements using segmentation software were not affected by the absence of contrast injection or the presence of stent-graft.Key Points: • AAA volumetry by semiautomated segmentation is accurate on CT following endovascular repair. • AAA volumetry by semiautomated segmentation is accurate on unenhanced CT. • Standardization of the segmentation technique maximizes the reproducibility of volume measurements.